Changes of stage, predictive factors and adjuvant treatment modalities in seminomatous testicular cancer from 1987 to 2007 and their impact on the status of metastasis, recurrence-free and overall survival: a single-center analysis - Heinzelbecker, Julia; Katzmarzik, Michaela; Weiß, Christel; Trojan, Lutz; Michel, Maurice Stephan; Häcker, Axel (Urologia internationalis, 2011)
Introduction: To observe the changing presentation of seminomatous testicular cancer (STC), placing particular emphasis on predictive factors with a view to evaluating their impact on the status of metastasis, recurrence-free survival (RFS) and overall survival (OAS). Materials and Methods: 180 patients with STC were evaluated retrospectively. Four study periods were generated and compared for changes. The data were analyzed for predictive factors for metastasis. Mean follow-up was 83 months (range 10-246, patients alive = 146). Results: The number of STC patients increased constantly throughout 2007. From 1992 onwards, significantly more patients were diagnosed as being in CS1 (p = 0.001). The odds ratio (OR) of metastasis was significantly higher for pT3 than pT2 STC (OR 12.4 vs. 1.7; p = 0.003); pT1 tumors showed a lower risk factor. The 10- and 15-year RFS were 91 and 85%, respectively. Patients in clinical stages higher than CS1 (CS>1) had significantly reduced RFS (p < 0.001). The 5- and 10-year OAS were 97 and 96%, respectively. Patients in CS>1 had significantly reduced OAS rates (p = 0.013). Conclusions: The number of STC cases is increasing, particularly in the case of patients in CS1. This emphasizes the need for surveillance regimens and makes the evaluation of predictive factors for metastasis, recurrence and survival essential.
Gesehen am 04.10.2022